Methanogenesis in Big Soda Lake, Nevada: an Alkaline, Moderately Hypersaline Desert Lake - Oremland, Ronald S. (1982)
Incubated sediment slurries from Big Soda Lake, Nevada, produced significant levels of CH(4), and production was inhibited by 2-bromoethanesulfonic acid and by autoclaving. Methane production was stimulated by methanol, trimethylamine, and, to a lesser extent, methionine. Surprisingly, hydrogen, acetate, and formate amendments provided only slight or no stimulation of methanogenesis. Methane production by sediment slurries had a pH optimum of 9.7. A methanol-grown enrichment culture containing a small, epifluorescent coccus as the predominant organism was recovered from sediments. The enrichment grew best when FeS or autoclaved sediment particles were included in the media, had a pH optimum of 9.7, and produced (14)CH(4) from (14)CH(3)OH. The methane formed by methanolgrown enrichment cultures was depleted in (13)C by 72 to 77‰ relative to the methanol.